BRACHIOPODI BATIALI NEL PLIOCENE E PLEISTOCENE DI SICILIA E CALABRIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The present paper considers the brachiopod fauna collected in upper bathyal sediments of Pliocene/Pleistocene ages in Eastern Sicily and Southern Calabria. For the Pleistocene, also deep circalittoral environments are included.
Keywords: Brachiopoda; Bathyal; Pliocene; Pleistocene; Taxonomy; Paleoecology; Sicilia; Calabria; Mediterraneo.